The Ca2+-binding protein parvalbumin: molecular cloning and developmental regulation of mRNA abundance. - Berchtold, M W (1985)
Parvalbumin (PV) is a Ca2+-binding protein found only in vertebrates. It is postulated to serve as a soluble relaxing factor in fast mammalian muscle. We have isolated a rat PV cDNA clone and used this as a probe to examine changes in PV mRNA during muscle and brain development. A cDNA library was constructed in PUC8/PUC9 plasmid vectors from adult poly(A)+ RNA isolated from rat gastrocnemius muscle. The library was screened with a 17-mer oligonucleotide encoding amino acids 28-33 of rat PV. One recombinant (9f) was confirmed as a PV clone by DNA sequencing and was shown to contain 73% of the protein coding sequence. Hybridization of clone 9f to RNA separated by electrophoresis revealed two species 700 and 1100 nucleotides long but genomic blotting indicates that PV may be a single copy gene. Highest levels of PV mRNA are found in the gastrocnemius, which is a fast contracting/relaxing muscle. Skin contains the next highest amount of PV mRNA followed, in order, by brain and the slow twitch soleus muscle. Rat muscle PV mRNA levels increase 15- to 20-fold between postnatal days 4 and 20 as measured by dot blot hybridization of total RNA, whereas only a slight increase was observed when young and adult brains were compared. The changes in PV mRNA during development appear to be selective, because mRNA coding for the structurally homologous Ca2+-binding protein calmodulin (CaM) was found to change only slightly in muscle. However, CaM mRNA levels decrease during the early days of brain ontogeny. Thus, the mRNAs that encode the homologous Ca2+-binding proteins PV and CaM appear to be developmentally regulated in a tissue-specific manner.